Pleuropulmonary Blastoma: A Single-center Case Series of 6 Patients. Issue 8 (November 2017) - Pierce, Janie M.; LaCroix, Priscilla; Heym, Kenneth; Bowman, William P.; Margraf, Linda; Iglesias, Jose; Ray, Anish
Abstract : Pleuropulmonary blastoma (PPB) is a rare malignancy of childhood which when left untreated often shows pathologic progression resulting in a more aggressive neoplasm with an increasingly poor prognosis. Because of this it is important to diagnose and initiate treatment early. However, early stage PPB can appear as a cystic lung lesion on imaging and can be easily misdiagnosed given the rarity of the malignancy. Moreover, current therapeutic guidelines for these lesions are not well established, making treatment decisions and management difficult for clinicians. DICER1 mutations are known to be present in a majority of PPBs with or without a germline mutation and may be part of a familial tumor predisposition syndrome. The clinical, pathologic, and genetic data of 6 patients are summarized here. Two patients with type I PPB and 4 patients with type II PPB underwent surgical and chemotherapeutic treatment and all are alive and without recurrence 1 to 13 years after treatment. With increasing awareness of PPB, it is important for clinicians to consider this malignant entity in the evaluation and treatment of patients presenting with a cystic lung abnormality, especially in cases with a history strongly suggestive of a DICER1 mutation.